Demographic and Radiographic Characteristics Associated with the Occurrence of Impacted Third Molars in Indonesian Patients: A Retrospective Study - Indra Hadikrishna; Melita Sylvyana; Madhuri Pattamatta; Folli Mulyawati; Tantry Maulina (MDPI AG, 2024)
An impacted third molar is one of the most common abnormalities of the tooth position, impacting patients and their quality of life. Based on the impact and the invasive removal procedure, this study aimed to evaluate the characteristics of impacted third molars based on their radiographic features as well as their association with demographic characteristics. Outpatient dental records of the oral and maxillofacial surgery department of Hasan Sadikin Hospital, Bandung, Indonesia, from 1 January 2018 to 31 December 2019, were sorted, and relevant clinical and demographic data and panoramic radiographic examination results were extracted from these records. All data were then tabulated and analyzed by using SPSS version 29. As many as 3019 impacted third molars were identified. Our findings suggested the association between age to the occurrence of impacted third molars where patients aged between 17 and 29 years old showed high occurrences of impacted third molars. Male patients with impacted third molars are more likely to have multiple impacted third molars, while this risk decreases in females. Radiographic examination showed that the mesioangular position is the most common position for mandibular third molars. The variation in high occurrences of the impacted third molar is associated with several demographic factors.